Effect of Oriented Assemblies of SrTiO3 with Exposed (200) Plane on Photocatalytic Hydrogen Evolution. Issue 11 (1st October 2022) - Vijay, Aditi; Priya S, Shanmuga; Terranova, Umberto; Maity, Madhusudan; Vaidya, Sonalika
Abstract: This study aims to investigate the effect of crystallographic orientation of the assemblies of SrTiO3 (formed on a glass substrate) on photocatalytic hydrogen evolution. For this, we have successfully synthesized nanocubes of SrTiO3 through a hydrothermal method. Assemblies on the glass substrate were formed by using functionalized/non‐functionalized oxide over functionalized/non‐functionalized glass substrate. The functionalization of the oxides and the glass substrate was carried out using IPTMS (3‐iodopropyltrimethoxy silane). Uniform assemblies of nanocubes of SrTiO3 with the particles oriented with (200) plane as the exposed surface were formed. The performance of these oriented assemblies was evaluated for photocatalytic hydrogen evolution reaction. Theoretical studies were carried out to understand the mechanism of photocatalytic hydrogen evolution over the oriented assemblies of SrTiO3 . Abstract : The orientation of the assembly of SrTiO3 nanostructures affects photocatalytic hydrogen evolution reaction.